Tear-Film Evaporation Rate from Simultaneous Ocular-Surface Temperature and Tear-Breakup Area. Issue 1 (January 2018) - Dursch, Thomas J.; Li, Wing; Taraz, Baseem; Lin, Meng C.; Radke, Clayton J.
Abstract : SIGNIFICANCE: A corneal heat-transfer model is presented to quantify simultaneous measurements of fluorescein tear-breakup area (TBA) and ocular-surface temperature (OST). By accounting for disruption of the tear-film lipid layer (TFLL), we report evaporation rates through lipid-covered tear. The modified heat-transfer model provides new insights into evaporative dry eye. PURPOSE: A quantitative analysis is presented to assess human aqueous tear evaporation rate (TER) through intact TFLLs from simultaneous in vivo measurement of time-dependent infrared OST and fluorescein TBA. METHODS: We interpret simultaneous OST and TBA measurements using an extended heat-transfer model. We hypothesize that TBAs are ineffectively insulated by the TFLL and therefore exhibit higher TER than does that for a well-insulting TFLL-covered tear. As time proceeds, TBAs increase in number and size, thereby increasing the cornea area-averaged TER and decreasing OST. Tear-breakup areas were assessed from image analysis of fluorescein tear-film-breakup video recordings and are included in the heat-transfer description of OST. RESULTS: Model-predicted OSTs agree well with clinical experiments. Percent reductions in TER of lipid-covered tear range from 50 to 95% of that for pure water, in good agreement with literature. The physical picture of noninsulating or ruptured TFLL spots followed by enhanced evaporation from underlying cooler tear-film ruptures is consistent with the evaporative-driven mechanism for local tear rupture. CONCLUSIONS: A quantitative analysis is presented of in vivo TER from simultaneous clinical measurement of transient OST and TBA. The new heat-transfer model accounts for increased TER through expanding TBAs. Tear evaporation rate varies strongly across the cornea because lipid is effectively missing over tear-rupture troughs. The result is local faster evaporation compared with nonruptured, thick lipid–covered tear. Evaporative-driven tear-film ruptures deepen to a thickness where fluorescein quenching commences and local salinity rises to uncomfortable levels. Mitigation of tear-film rupture may therefore reduce dry eye–related symptoms. Abstract : Supplemental digital content is available in the text.